2013
DOI: 10.1007/s12288-013-0290-z
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Cyclophosphamide Therapy in Refractory Warm Autoimmune Hemolytic Anemia: A New Perspective

Abstract: Treatment of steroid refractory autoimmune hemolytic anemia (AIHA) is challenging especially with no evidence based consensus guide lines and limited resources. The aim of this study was to evaluate the efficacy of pulse cyclophosphamide therapy in patients with severe refractory warm AIHA. The prospective study was designed to evaluate the efficacy of pulse cyclophosphamide-1 g/month for four consecutive months-in 17 patients (10 males and 7 females) with severe refractory warm AIHA [13 primary AIHA and 4 (fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In another study, 4/7 patients responded but no patient achieved a steroid-independent sustained response [82]. Two studies reported success with intravenous cyclophosphamide [110,111].…”
Section: How Should Corticosteroids Be Tapered and What Is A Steroid mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, 4/7 patients responded but no patient achieved a steroid-independent sustained response [82]. Two studies reported success with intravenous cyclophosphamide [110,111].…”
Section: How Should Corticosteroids Be Tapered and What Is A Steroid mentioning
confidence: 99%
“…All patients responding to either 50 mg/kg (ideal body weight)/day for 4 days (4 had primary warm AIHA) without autologous stem cell transplantation or 1 g monthly for 4 months (13 had primary warm AIHA). Important side effects include myelosuppression, infections, urotoxicity, secondary malignancy, and infertility [111].…”
Section: How Should Corticosteroids Be Tapered and What Is A Steroid mentioning
confidence: 99%
“…50–100 mg daily) with or without prednisolone, there are few data on dosing or efficacy and, given its mutagenic potential, oral cyclophosphamide cannot be recommended over second line steroid‐sparing agents. Higher intravenous doses also appear effective, for example 50 mg/kg/day for 4 days (Moyo et al , ) or 1 g monthly for 4 months (Thabet & Faisal, ).…”
Section: Non‐emergency Managementmentioning
confidence: 99%
“…The more commonly used treatments along with their corresponding dosing schedules are displayed in Table 1. [36][37][38][39][40][41][42] Patterns of care studies are not available, but single-agent rituximab is perhaps the most commonly used treatment in this setting and is our first choice after splenectomy relapse. In a meta-analysis of 21 studies that investigated rituximab, the overall response (OR) and CR rates were 79% and 42%, respectively.…”
Section: What Is the Value Of Splenectomy?mentioning
confidence: 99%